Establishing an Inclusive Islamic Education Ecosystem to Confront Religious Exclusivism Challenges in Educational Institutions - Ahmad Wildan Thobibi Bahja; Luqman Hakim (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
The rise of digitalization has led to significant changes, particularly in education, by enabling unlimited access to diverse knowledge and cultures. However, this accessibility also poses risks for younger generations, potentially exposing them to exclusive and intolerant religious teachings that hinder their acceptance of diversity. Islamic education is demanded to seek alternative solutions in facing these challenges by building an inclusive Islamic education ecosystem. This research aims to examine and analyze the concept of an Inclusive Islamic Education ecosystem, the crucial role of the inclusive Islamic education ecosystem in addressing religious exclusivism in educational institutions, and efforts to address the challenge of religious exclusivism in educational institutions by building an inclusive Islamic education ecosystem. This research is a type of descriptive qualitative study. The rationalistic approach is used to analyze the problems holistically. The method used is library research. The research findings indicate that: (1) the concept of an inclusive Islamic education ecosystem essentially originates from the teachings of Islam as universal and has been exemplified by the Prophet Muhammad SAW in unifying the Madinah society, (2) an inclusive Islamic education ecosystem plays a crucial role for educational institutions in Indonesia in producing graduates who have firmness in Islamic faith and are free from religious exclusivism, (3) Efforts to address the challenges of religious exclusivism can be carried out by holistically building an inclusive Islamic education ecosystem involving several key elements, including the education curriculum, educators, students, learning models, parents and society.